Determinants of Intention to Use HIV Pre-exposure Prophylaxis and Condom Use Among a Sample of Cisgender Female Sex Workers Working Mostly Outdoors in Madrid, Spain. - Vazquez Guillamet, Laia J.; Valencia, Jorge; Ryan, Pablo; Cuevas-Tascón, Guillermo; del-Olmo-Morales, Miguel Angel; Cobo, Ines; Lazarus, Jeffrey V.; Chevance, Guillaume (Archives of Sexual Behavior, 2024)
There is scant knowledge regarding pre-exposure prophylaxis (PrEP) use among female sex workers (FSWs) in Europe. Spain recognized FSWs as a population at high risk of acquiring HIV and granted them subsidized access to PrEP when the medication first became nationally available in 2019. Nevertheless, FSWs represented just 0.2% of PrEP users in 2022. A total of 102 HIV-negative FSWs reached through field activities of local NGOs located in Madrid were interviewed between January and March 2022. Participants were selected through convenience sampling over a fixed recruitment period. FSWs completed a 73-item survey with questions about individual, occupational, social, and structural determinants. The objective of this study was to identify (1) the prevalence of intention to use oral PrEP and its determinants, and (2) the prevalence of inconsistent condom use, which is the risk factor that qualifies FSWs for subsidized PrEP in the national health system, and its determinants. Importantly, the study sample overrepresented street-based FSWs (71.6%). A quarter (25.5%) of the study participants used condoms inconsistently. PrEP awareness was low (9.8%), but intention to use PrEP was high (72.5%). Intention to use oral PrEP was significantly associated with feeling protected against HIV by taking PrEP and perceiving insufficient protection by condom use alone. Inconsistent condom use was significantly associated with frequent heroin/cocaine use, having clients who inject drugs, and willingness to take PrEP despite it not protecting 100% against HIV infection. FSWs, in this specific sample, are likely to benefit from targeted PrEP awareness campaigns and implementation projects that prioritize those who use drugs and are more likely to engage in condomless sex.